Economic fluctuations and retirement of older employees - Daniel Hallberg (Institute for Labour Market Policy Evaluation (IFAU), 2008)
This paper studies the way in which labor market fluctuations affect the transition to early retirement among older employees in Sweden via the practice of negotiated pensions. The results indicate that downturns (upturns) in aggregated industry employment increases (decreases) the probability of early retirement. This result is driven by the public sector; in general the evidence is much weaker in the private sector. The results also suggest that the replacement levels immediately after early retirement are higher during declining as well as expanding industry employment. The results support an interpretation that 1) the employer and employee agreed on special early retirement pensions, and 2) that these were used in order to persuade older employees to quit voluntarily, but also that they worked to reward older employees.
Keywords: J14; J21; J23; J26; 330; Retirement; fluctuating markets; buy-outs; demand for old workers; Ältere Arbeitskräfte; Altersgrenze; Alterssicherung; Erwerbspersonenpotenzial; Arbeitsnachfrage; Schweden